2021
DOI: 10.1039/d1py01024g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the preparation of semifluorinated polymers

Abstract: Synthesis of semifluorinated polymers containing fluorous groups on the backbone or as side chains is an increasingly popular field of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…It has been reported that small amounts of functionalization can lead to pronounced modifications of the polymer's material properties (e.g., adhesion, surface tension). [194][195][196][197][198][199] For example, Hartwig and co-workers demonstrated that the selective thermocatalytic oxidation of CH bonds in PE at 120 °C could imbue adhesive properties unseen in the unmodified materials, which transformed existing commodity polyolefins into highvalue materials without affecting their inherent thermal stability and mechanical strength. [198] Very recently, Fazekas et al reported a versatile radical-mediated CH functionalization of polyolefins upon mild heating, which upcycled postconsumer waste PE into high-value polyolefin ionomers that were much tougher and stronger than the parent plastics.…”
Section: General Considerations and Mechanismsmentioning
confidence: 99%
“…It has been reported that small amounts of functionalization can lead to pronounced modifications of the polymer's material properties (e.g., adhesion, surface tension). [194][195][196][197][198][199] For example, Hartwig and co-workers demonstrated that the selective thermocatalytic oxidation of CH bonds in PE at 120 °C could imbue adhesive properties unseen in the unmodified materials, which transformed existing commodity polyolefins into highvalue materials without affecting their inherent thermal stability and mechanical strength. [198] Very recently, Fazekas et al reported a versatile radical-mediated CH functionalization of polyolefins upon mild heating, which upcycled postconsumer waste PE into high-value polyolefin ionomers that were much tougher and stronger than the parent plastics.…”
Section: General Considerations and Mechanismsmentioning
confidence: 99%
“…With promising initial amination results on a lower molar mass polymer sample, we turned our attention to higher molar mass 1,4‐PBD (M n,MALS =32 kDa) (Table S1) for more challenging upcycling using trifluoromethane sulfonamide ( TFMS ) and trifluoropropyl sulfonamide ( TFPS ). Polymer semifluorination is known to engender the resulting materials with novel thermal and surface coating properties [48] . Subsequent 19 F NMR spectroscopy analysis (Figure 2C) of upcycled telechelic 1,4‐PBD bearing trifluoromethyl phenyl chain ends (Figure S33–S36) revealed sulfonamide densities ranging between D NMR =5.4–41 mol % [Eqs.…”
Section: Figurementioning
confidence: 99%
“…Polymer semifluorination is known to engender the resulting materials with novel thermal and surface coating properties. [48] Subsequent 19 S3)]. We attempted to corroborate these NMR spectroscopy data with complementary absolute molar mass determination using analytical GPC coupled with a multiangle light scattering (MALS) detector, but these data proved to be unreliable.…”
mentioning
confidence: 99%
“…1 The installation of fluorine atoms may endow the polyester with excellent thermal and surface properties, such as low surface energy, good hydropho-bicity and oleophobicity, high thermal stability, and solvent resistance due to the large bond energy of C-F and the small radius of the fluorine atom. 2,3 Consequently, fluorinated polyesters have shown great potential in textiles, antifouling coatings, optical waveguide devices, biomedical devices, etc. 2,[4][5][6][7][8][9][10][11][12][13][14][15] Nevertheless, studies on fluorinated polyesters were few compared to other fluoropolymers, because of the difficulty in synthesis.…”
Section: Introductionmentioning
confidence: 99%